Compositeelectrocatalysts containing valve metal oxides: Synthesis, physico-chemical properties and electrocatalytic activity - Velichenko, A. B.; Kasian, O. I.; Knysh, V. A.; Luk'yanenko, T. V. (Voprosy Khimii i Khimicheskoi Tekhnologii, 2015)
It was found that the semiconductor properties of composite TixO/Pt-electrodes depend on thesubstrate's nature, the quantity of electrodeposited platinum and the treatment temperature. During the electrodeposition of thin platinum layer on the titanium substrate, the formation of composite coating containing titanium in metallic and oxide forms, platinum and TixPty-intermetallic phase is observed. The thermal treatment leads to morphology changes due to sintering and mobility of Pt along and deep into substrate. The morphology of TixO/Pt and phase composition of EbonexT/Ptdepend on the quantity of electrodeposited platinum, temperature and duration of treatment. New phases of systems Ti-Pt and Ti-Pt-O were identified. The reduction peak of platinum oxides on the cathodic branch of voltammograms could be correlated with electrocatalytic activity of thermally treated TixO/Pt-electrodes.It was shown that the particles of dispersed phase are charged positively in the suspension electrolyte and they may aggregate in the presence of Pb2+ ions. The addition of sodium dodecylsulfate in the electrolyte leads to recharge dispersed particles due to specific adsorption. The enhanced colloid-chemical mechanism of the composite electrodeposition from suspension electrolytes was proposed. The delivery of dispersed particles to the surface electrode occurs by both diffusion and migration. The content of foreign oxides in the composite depends on colloidal properties, electrolyte composition, particle and electrode charge and deposition conditions. The obtained composite anodes have 2-4 longer life time in comparison with conventional PbO2 electrodes and it is proposed to use them as electrocatalysts for various electrochemical processes.
CRIS-Team Scopus Importer:2023-03-07
Keywords: Composite anodes; Electrocatalytic activity; PbO; Platinum; Valve metal oxides